2004
DOI: 10.1136/jcp.2004.016246
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between clinical and postmortem diagnoses in Jamaica: a study from the University Hospital of the West Indies

Abstract: Aims: It has previously been shown that the low necropsy request rate at the University Hospital of the West Indies (UHWI) in Jamaica (35.3%) results primarily from clinicians' confidence in clinical diagnoses and laboratory investigations. This study aimed to determine the rates of discrepancy between clinical and necropsy diagnoses at the UHWI, because many previous studies from other institutions have shown persistent high rates of discrepancy, despite advances in medical investigative technology over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
5
22
1
2
Order By: Relevance
“…We not observed a significant correlation between the last admission unit and the level of agreement, in contrast to Gibson et al 18 that found the lowest frequent of concordant diagnoses in the emergency room (33.6%) and the highest (68.4%) in the intensive care unit. The elevated discrepancy rates with advancing patient age evidenced by this author 18 was not observed in our results and in analysis described previously 3,12 . In cases with a poor prognosis, which are more common in elderly, it is possible that the physician and the patient's relatives decide not to proceed with clinical investigations, which can contribute to a greater chance of misdiagnosis in the older population 9 .…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…We not observed a significant correlation between the last admission unit and the level of agreement, in contrast to Gibson et al 18 that found the lowest frequent of concordant diagnoses in the emergency room (33.6%) and the highest (68.4%) in the intensive care unit. The elevated discrepancy rates with advancing patient age evidenced by this author 18 was not observed in our results and in analysis described previously 3,12 . In cases with a poor prognosis, which are more common in elderly, it is possible that the physician and the patient's relatives decide not to proceed with clinical investigations, which can contribute to a greater chance of misdiagnosis in the older population 9 .…”
Section: Discussioncontrasting
confidence: 41%
“…There was agreement between the clinical and pathological diagnoses in 33.8% of these cases. Respiratory diseases, in particular pneumonia, were the main causes of death diagnosed in discordant acute myocardial infarction cases, probably due to the similarities in both the clinical symptoms of patients and occasionally radiological signs between the two diseases 6,18 . Most of these patients were hospitalized because of pulmonary infections and evolved with an acute aggravation of the symptoms which was attributed to the pulmonary infection and not acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the impact of medical imaging in reliably recognizing certain clinical entities remains unproven. 2,3,19 Moreover, overreliance on these advanced techniques, especially radiologic imaging, has been shown to occasionally contribute directly to inaccurate or unrecognized diagnoses. 12 discrepant diagnoses were the result of a misleading diagnostic test result.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] However, several studies have documented a decrease in the autopsy rate and in the importance given to autopsy by clinicians. 6,7 The causes for the decreasing autopsy rate are diverse and include technological advances in clinical testing and imaging, fear of potential medicolegal problems that could result from discrepant findings, and a declining interest in autopsies among pathologists.…”
mentioning
confidence: 99%
“…Concordance between ante-mortem and post-mortem diagnoses was seen in 64 patients (74%), which is consistent with other studies reported in the literature. [2][3][4][5][6][7] Unsuspected medical conditions relevant to death that were suggested by post-mortem examination and were not recorded as known during life are shown in Table 2.…”
Section: Pulmonary Thromboembolism 5 Bronchopneumoniamentioning
confidence: 99%